Program Pencegahan Sekunder Dengan Fisioterapi Pada Penderita Osteoarthritis Knee Di Puskesmas Setabelan - Farah Hanifah Setiarahmawati; Farid Rahman; Yusuf Arianto (Pusat Riset dan Inovasi Nasional, 2023)
Setabelan Village, located in Banjarsari Sub-district, is one of the four working areas of the Setabelan Health Center. The village experiences a high incidence of Osteoarthritis knee cases in elderly women, with 28 cases per month and 246 cases per year. The main complaint among patients is knee pain. To address this issue, a program was implemented to educate and provide understanding on how to manage knee osteoarthritis, as well as home-based exercise. The program involved counseling sessions on osteoarthritis knee health promotion, using leaflets as a counseling medium. The target participants were the elderly members of Pos Lansia Wijaya Kusuma. The author conducted a pre-test and post-test to evaluate the participants’ level of understanding. The results showed a significant increase in understanding, with the participants’ average questionnaire score increasing from 1.57 in the pre-test to 5.57 in the post-test. This indicates a 4.00 increase in understanding among the participants of Pos Lansia Wijaya Kusuma.